Pengaruh Manajemen Pendidikan terhadap Hasil Belajar Siswa di Sekolah Dasar Negeri 164526 Tebing Tinggi - Irmina Pinem; Darinda Sofia Tanjung; Nova Florentina Ambarwati; Meikardo Samuel Prayuda; Regina Sipayung; Sari Natalia (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
This study aims to analyze the effect of educational management on student learning outcomes at State Elementary School 164526 Tebing Tinggi. Educational management is understood through the functions of planning, organizing, actuating, controlling, and evaluating, while student learning outcomes were obtained from documentation of formative assessment, summative assessment, and report-card scores. The study employed a quantitative approach using an ex post facto method and a correlational design. The sample consisted of elementary school teachers selected through simple random sampling. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, as well as documentation of student learning outcomes. The data were analyzed using descriptive statistics, prerequisite tests, and simple linear regression. The findings show that educational management has a positive effect on student learning outcomes. Better implementation of management functions is associated with more directed instructional management, more consistent academic supervision, and the use of evaluation as a basis for improvement. These findings indicate that strengthening school management can serve as a practical strategy for improving instructional quality and student learning outcomes in elementary schools. Therefore, this study contributes to the field of elementary educational management by explaining the relationship between school management quality and student learning achievement.